Pre-harvest application of 2-(3-chlorophenoxy) propionic acid on pineapple plants - Oliveira, Fernanda Soares; Maia, Victor Martins; Pegoraro, Rodinei Facco; Carvalho, Danielle Mota; Souza, Mirna Ariane Taveira de Sousa; Mota, Mauro Franco Castro Mota (Comunicata Scientiae, 2024)
The application of plant regulators such as exogenous auxin may provide effects on the translocation of carbohydrates to plant sinks, which may result in larger parthenocarpic fruits. The objective of the study was to evaluate the effects of the application of 2-(3-chlorophenoxy) propionic acid on the growth and quality of pineapple fruits. The experiment was carried out in a randomized block design. After floral induction, 2-(3-chlorophenoxy) propionic acid (CPA) was applied directly on the inflorescences at the following doses: 0 mg L-1; 40.0 mg L-1; 80.0 mg L-1; 120.0 mg L-1 and 160.0 mg L-1. Growth evaluations continued until 84 days after application, measuring fruit length (cm) with and without crown, crown length (cm), leaf D dry matter, fruit weight with and without crown (g), calculating if also, the absolute and relative growth rates. The post-harvest and quality characteristics of the fruits were also evaluated, as well as the harvest index. The application of CPA significantly reduces the length and weight of the crown of the fruits, however, the exogenous application of auxin provided an increase in the weight of the fruit. Regarding the post-harvest analysis, the application of CPA reduced the content of soluble solids in the fruit pulp.